Parliamentary dimension of the Polish presidency - Czachór, Zbigniew (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The process of European integration has contributed to a significant concentration of member states’ political power in the hands of a bureaucratic-executive elite. This has been a result of European Union institutions discriminating in favor of national administrations rather than respective parliamentary institutions. Thereby, a European pattern of supremacy of the executive elite has been established, based on a mechanism of strict cooperation, and a system of institutional links between European and national bureaucracies. Unfortunately, national parliaments and the European Parliament were significantly late in responding to this process. This resulted in a lack of efficient methods to monitor political decision-makers and officials as regards their activity in the European forum. Not only has the integration system undermined the general powers of nation-states, but it has created a powerful bureaucracy whose competences have significantly increased on account of its international connections.